PENGARUH LINGKUNGAN TOKO TERHADAP IMPULSE BUYING DENGAN EMOSI POSITIF SEBAGAI VARIABEL INTERVENING - Maharanie, Regina Putri; Suharyono, Suharyono; Yulianto, Edy (FIA UB, 2020)
This study aimed to investigate the influence of independent variables (sosial factors, design factors and ambient factors) towards dependent variable (impulse buying) which was mediated partially by positive emotion variable on the visitors of Transmart Carrefour Banjarmasin City. For research design, this study used quantitative method by employing an explanatory research. Researchers used primary data obtained from direct distribution questionnaire and utilized purposive sampling method as sampling technique. There were 118 respondents who where involved due to their suitability with study population. Then, the data was analysed by using SEM-PLS method. The results of this study indicated that store’s environment influence (social factor, design factor, and ambient factors) had positive and significant effect on visitors’ positive emotion and impulse buying. In addition, the indirect influence (social factor, design factor, and ambient factors) which was mediated by positive emotion on impulsive purchases and positive emotion was considered to be partial mediator variable.